The Viennese Coffee House as a Living Environment and Mirror of social Changes, using the Example of Stefan Zweig's novella Buchmendel - COŞAN, LEYLA (My University, 2022)
In his novella Buchmendel (1929), Stefan Zweig (1881-1942) refers to the tradition of the coffee house as an explicit place of cultural and social exchange in the 20th century Vienna. The aim of this study is to show the Viennese coffee house tradition not only as a breeding ground for social developments, but also as a kind of microcosm in which the oscillations of social life are reflected. The novella Buchmendel (1929) will be used to analyse the coffee house culture of Viennese society as a seismograph of social changes. The main focus of the study is the story of the protagonist Buchmendel, whose life circumstances will be described and analysed against the backdrop of the Viennese coffee house tradition culture.
Keywords: Sosyal ve Beşeri Bilimler; Dil ve Edebiyat; Social Sciences and Humanities; Philology; DİL VE DİLBİLİM; Sanat ve Beşeri Bilimler; Sanat ve Beşeri Bilimler (AHCI); EDEBİYAT; DİLBİLİM; LANGUAGE & LINGUISTICS; ARTS & HUMANITIES; Arts & Humanities (AHCI); LITERATURE; LINGUISTICS; Dilbilim ve Dil; Edebiyat ve Edebiyat Teorisi; Koruma; Dil ve Dilbilim; Sanat ve Beşeri Bilimler (çeşitli); Genel Sanat ve Beşeri Bilimler; Sosyal Bilimler ve Beşeri Bilimler; Linguistics and Language; Literature and Literary Theory; Conservation; Language and Linguistics; Arts and Humanities (miscellaneous); General Arts and Humanities; Social Sciences & Humanities; Stefan Zweig; Buchmendel; Viennese Coffee House; Social Change; JEWISH IDENTITY